PELATIHAN ARDUINO KEPADA REMAJA DESA SINDANGJAYA GUNA MENUNJANG KOMPETENSI DALAM BIDANG TEKNOLOGI DAN OTOMASI - Firman Choiri Okta; Aningsih Aningsih; Rizki Ridha Kusuma (Universitas Islam 45 Bekasi, 2023)
The district of Bekasi in West Java province has good industrial potential and economic growth, but there are still issues of poverty in some areas, including the village of Sindangjaya. The competency and skills level of the workforce in Sindangjaya is also still inadequate. Data from the BPS shows that around 50% of the population in Bekasi is of productive age, but many of them lack knowledge and skills in technology, such as the students in the Islamic boarding school in Sindangjaya. This Arduino training is expected to provide electronic technology knowledge and skills to the students and enrich the education curriculum by adding technology and automation-related subjects. This training can also provide valuable experience for students in terms of community service and developing technology and automation skills, as well as offering opportunities to work in industries that require Arduino expertise. Th e method used for this Arduino training program is community education and training. The program's implementation results show that most participants have understood how to use Arduino and create simple electronic circuits. This can be seen from the participants' success rate in creating flip-flop circuits with push buttons and light sensors, as well as the evaluation data of their understanding after completing the training. The conclusion drawn from this training is that the program is very important and relevant to current community needs. The program is effective in improving the technical understanding and skills of participants in using technology and automation.